Protocol for an implementation study of group metacognitive therapy for anxiety and depression in NHS cardiac rehabilitation services in England (PATHWAY-Beacons) - Wells, Adrian; Reeves, David; Belcher, Andrew; Wilson, Paul; Doherty, Patrick; Capobianco, Lora (Frontiers in Health Services, 2024)
BackgroundCardiac rehabilitation (CR) services aim to improve heart disease patients’ health and quality of life and reduce the risk of further cardiac events. Depression and anxiety are common among CR patients but psychological treatments have usually had small effects. In contrast, the recent NIHR-funded PATHWAY trial found that group Metacognitive Therapy (MCT) was associated with improvements in anxiety and depression when added to CR and was more effective than usual CR alone. The next stage is to test implementation of MCT within the National Health Service through the creation of a network of CR beacon sites. The study will test the quality of data capture following addition of a new MCT data-field to the national audit of cardiac rehabilitation (NACR), examine level of adoption at sites, examine mental health outcomes benchmarked against usual CR and the PATHWAY data, examine the enablers and barriers to implementation and the expected resource requirements. The study has been registered: NCT05956912 (13th July, 2023).MethodsBeacon sites will be recruited as preliminary adopters of group MCT from NHS CR services in England. A national invitation for expressions of interest from CR services will be issued and those meeting eligibility criteria will be considered for inclusion. Two staff at each site will receive training in MCT, and mixed-methods will be used to address questions concerning the quality of patient data recorded, level of adoption at sites, the characteristics of patients attending MCT, the impact of adding MCT to CR on mental health outcomes, and patient, healthcare staff and commissioner views of barriers/enablers to implementation. Exploration of implementation will be informed by Normalisation Process Theory.DiscussionThe study will support development of an NHS roll-out strategy, assess the mental health outcomes associated with MCT, examine treatment fidelity in real-world settings, and evaluate revised data collection structures that can be used to assess the impact of national-level implementation. Trial RegistrationNCT05956912; 13th July 2023.